The Loss of Nandong Culture in Sambay Village, West Aceh: A Sociology Perspective - Andi Fadinul (HM Publisher, 2020)
Nandong is a song usually sung by Padang people who come to trade to the island of Simeulue. Nandong poetry is sung in the form of rhymes and describes the story of human life, but over time, the poems conveyed by intelligent people are compiled into art called Nandong. Nandong poetry tells the story of human life and is displayed in wedding events to be entertained and give advice to those who are married. However, at this time, the preservation of Nandong culture seems to be fading due to the development of modern musical instruments so that local culture is rarely displayed. This study will describe the factors causing the loss of Nandong culture in Sambay village, West Aceh.